Characterizing transmissive diamond gratings as beam splitters for the hard X‐ray single‐shot spectrometer of the European XFEL. (10th May 2019) - Kujala, Naresh; Makita, Mikako; Liu, Jia; Zozulya, Alexey; Sprung, Michael; David, Christian; Grünert, Jan
Abstract : Grating structures with 150 nm pitches were fabricated on free‐standing CVD diamond membranes supported by a silicon frame. The efficiencies and structural homogeneity of the gratings were measured with synchrotron X‐rays at different photon energies. Abstract : The European X‐ray Free Electron Laser (EuXFEL) offers intense, coherent femtosecond pulses, resulting in characteristic peak brilliance values a billion times higher than that of conventional synchrotron facilities. Such pulses result in extreme peak radiation levels of the order of terawatts cm −2 for any optical component in the beam and can exceed the ablation threshold of many materials. Diamond is considered the optimal material for such applications due to its high thermal conductivity (2052 W mK −1 at 300 K) and low absorption for hard X‐rays. Grating structures were fabricated on free‐standing CVD diamond of 10 µm thickness with 500 µm silicon substrate support. The grating structures were produced by electron‐beam lithography at the Laboratory for Micro‐ and Nanotechnology, Paul Scherrer Institut, Switzerland. The grating lines were etched to a depth of 1.2 µm, resulting in an aspect ratio of 16. The characterization measurements with X‐rays were performed on transmissive diamond gratings of 150 nm pitch at the P10 beamline of PETRA III, DESY. In this paper, the gratings are briefly described, and a measured diffraction efficiency of 0.75% at 6 keV in the first‐order diffraction is shown; the variation of the diffraction efficiency across the grating surface is presented.